2015
DOI: 10.1007/s11239-015-1246-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a concept for a personalized approach in the perioperative antiplatelet therapy administration/discontinuation management based on multiple electrode aggregometry in patients undergoing coronary artery surgery

Abstract: administration/discontinuation management. Despite emerging evidence on the widespread variability in platelet inhibitory response to APT, numerous PFT devices and heterogeneity in reporting study results hamper pooling of the evidence which in turn results with a lack of consensus in "on treatment" platelet reactivity associated with ischemic and bleeding events in perioperative phase. MethodsThe literature on multiple electrode aggregometry (Multiplate® ; Roche Diagnostics, Mannheim, Germany) in coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…To stimulate the aggregation, multiple agonists can be used to test different platelet activation pathways. An attempt has been made to determine a therapeutic window for APT dosage based on the Multiplate results in patients with coronary artery disease [37]. However, measuring platelet function by global aggregation measure approach is usually less specific to evaluate the effect of specific antiplatelet drug.…”
Section: Discussionmentioning
confidence: 99%
“…To stimulate the aggregation, multiple agonists can be used to test different platelet activation pathways. An attempt has been made to determine a therapeutic window for APT dosage based on the Multiplate results in patients with coronary artery disease [37]. However, measuring platelet function by global aggregation measure approach is usually less specific to evaluate the effect of specific antiplatelet drug.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative platelet function testing can be used to detect a residual platelet function defect in patients treated with antiplatelet drugs or other drugs that might impair platelet function in order to reduce the waiting time until surgery after cessation of ADP-receptor antagonists [78][79][80][81][82]. However, the intra-and post-operative changes in platelet function seem to be more significant and important for peri-operative bleeding management in patients undergoing cardiac surgery with CPB [47,60,[82][83][84][85]. Accordingly, platelet function testing results achieved after protamine administration demonstrated the best correlation with postoperative chest tube drainage and postoperative transfusion requirements that were dependent on the degree of platelet inhibition and the number of pathways inhibited [47].…”
Section: Korean J Anesthesiolmentioning
confidence: 99%
“…19 Petricevic et al also tried to define a therapeutic window for aspirin using aggregometry and reported that the lowest AA value to avoid bleeding was 20 U. 20 Our study showed that an AA value of 16.5 U exhibited an 83.3% specificity and a 50.8% sensitivity. Thus, our cutoff value is similar to those of previous reports.…”
Section: Discussionmentioning
confidence: 49%